Pengaruh Suplementasi β-Carotene terhadap Kadar Trigliserida Studi pada Tikus Wistar Diabetes Mellitus Tipe 2 yang Diberikan Pakan Tinggi Lemak dan Diinduksi Streptozotocin-Nicotinamide: The Effect of β-Carotene Supplementation on Triglyceride Levels Study on Type 2 Diabetes Mellitus Wistar Rats Fed High-Fat Diet and Induced Streptozotocin-Nicotinamide - Soviana, Elida; Aviarani, Tea; Arum, Puspito (Universitas Airlangga, 2025)
Background: Hypertriglyceridemia is associated with decreasing insulin sensitivity and increasing insulin resistance in type 2 diabetes mellitus. β-carotene has a cytoprotective effect that can improve and protect β-cells of the pancreas, resulting in increased insulin synthesis and secretion. β-carotene prevents the deleterious effects of uncontrolled glucose and lipid metabolism. Objectives: This research aimed to investigate the effect of β-carotene supplementation on triglyceride levels in high-fat diet and streptozotocin-nicotinamide induced Type 2 Diabetes Mellitus Wistar Rats. Methods: 18 Wistar rats were randomly divided into three groups: X1 (negative controls), X2 (positive controls), and X3 (STZ-NA+β-carotene 10 mg/KgBW). High-fat diet intervention was given 14 days before diabetic induction in X2 and X3 groups; the negative control group X1 was given standard feed. To condition Wistar rats to be type 2 Diabetes Mellitus, rats in groups X2 and X3 received intraperitoneal injections of Streptozotocin at a dose of 45 mg/KgBW and nicotinamide at a dose of 110 mg/kgBW. Supplementation of β-carotene was given by the nasogastric feeding tube method every 2 days within 30 days. Plasma Triglyceride levels were measured using GPO-PAP. The effect of triglyceride levels after β-carotene supplementation was tested with a statistical test using a paired t-test and one-way ANOVA. Results: Blood glucose levels in groups X2 and X3 increased by 188.34 g/dl and 186.34 g/dl after being injected with STZ and NA. There was a significant effect of triglyceride levels (p-value<0.001) after supplementation with β-carotene at a dose of 10 mg/kgBW. Serum triglyceride levels decreased by a mean of 21.90% or 28.42 mg/dl. Conclusions: This research revealed that the supplementation of β-carotene at a dose of 10 mg/kgBW every 2 days within 30 days by the nasogastric feeding tube method can lower triglyceride levels in diabetic Wistar rats.